Are We There Yet? The Need for Metrics to Help Us Get From Where We Are to Where We Need to Be - Ang, Rodolfo P (Archīum Ateneo, 2021)
The “Inspirational Paradigm for Jesuit Business Education” presents a vision for the future of business education, and the transformative effect it should have on our students and on society. But this Paradigm cannot move from inspiration to actualization unless we develop metrics that measure how we stand today relative to the goals of the paradigm, and our progress, over time, in attaining these goals. In this essay, the author proposes input scorecards to measure our coverage of the themes highlighted in the paradigm, and an output scorecard to measure our effectiveness in delivering the program outcomes implied in it. The author does not present a definitive measurement tool: merely a starting point for a deeper discussion of the metrics that we need to develop if we take this Inspirational Paradigm seriously.